ParPMC-mediated susceptibility to plum pox virus: vascular expression in Prunus armeniaca and functional validation through ortholog silencing in Nicotiana benthamiana - Polo-Oltra, Ángela; Sánchez-Navarro, Jesús A.; Berbel, Ana; Romero, Carlos; Zuriaga, Elena (Frontiers in Plant Science, 2025)
Sharka disease, caused by the Potyvirus plumpoxi (plum pox virus, PPV), is the primary limiting factor for stone fruit production globally, and the development of PPV-resistant cultivars is the most effective long-term strategy for controlling this disease. Recent studies have identified the Prunus armeniaca PPVres MATHd-containing (ParPMC) genes, part of a cluster of similar genes, as key host susceptibility factors essential for PPV infection in apricot. However, their specific functions remain largely unknown. This study examined the spatial expression patterns of the ParPMC1 and ParPMC2 genes, showing that they were primarily expressed in vascular bundle-rich tissues and were downregulated in resistant apricot cultivars. At subcellular level, both proteins localized in the nucleus and cytoplasm but ParPMC1 was distributed throughout the nucleus, whereas ParPMC2 appeared to be confined to the nuclear envelope. Orthology analyses revealed a “one-to-many” topology, indicating that a single ancestral gene duplicated after the emergence of the Rosaceae family, followed by additional tandem duplications and losses within Prunus species. To assess whether ParPMC downregulation contributed to PPV resistance, the ParPMC ortholog in Nicotiana benthamiana (NbPMC) was efficiently silenced using Tobacco Rattle Virus (TRV)-mediated Virus-Induced Gene Silencing (VIGS), resulting in a reduction in PPV infection. Overall, these results support the initial hypothesis that ParPMC1 and/or ParPMC2 function as host susceptibility genes in apricot, and their silencing may confer resistance to PPV. Moreover, their expression in conductive tissues suggests a potential role in the long-distance movement of the virus. This study marks an important first step in characterizing ParPMC genes and their role in PPV infection.